Effectiveness of Hypnosis for the Prevention of Anxiety During Coronary Angiography (HYPCOR study): a prospective randomized study - Laure Abensur Vuillaume; Charles Gentilhomme; Sandrine Weber; Nadia Ouamara; Julien Bayard; Mathieu Valla; Khalife Khalife; Christophe Goetz; Nazmine Guler (BMC, 2022)
Abstract Background Coronary angiography is the gold standard for the diagnosis of coronary artery disease. This intervention is nevertheless a source of anxiety for the patient both by its discomfort and by the consequences linked to the discovery of potential diseases. Objectives The aim of this study was to determine the effectiveness of hypnosis in reducing anxiety in patients undergoing coronary angiography. Methods One hundred sixty-nine patients with planned coronary angiography and no history of coronary angiography were randomized to a hypnosis or control group. Patients in the hypnosis group underwent a hypnosis session with self-hypnosis posthypnotic suggestions, while those in the control group had a conversational interview with the hypnotherapist. The primary endpoint was pre-exam anxiety level assessed by the Spielberger State-Trait Anxiety Inventory (STAI-Y A). Results Performing a hypnosis session did not result in a significant decrease in anxiety before the intervention. Age, high trait anxiety, high state anxiety the day before, and belief that hypnosis works in general were associated with increased anxiety before the procedure. No adverse events were reported after hypnosis. There was no statistically significant difference between the 2 groups for the occurrence of complications of the intervention. Conclusion In this study, performing a hypnosis session before coronary angiography did not reduce the state of anxiety measured just before the intervention. In all cases, the hypnotic experience appears to be positive for the patient, encouraging further research efforts. Trial registration The research protocol has been registered on the ClinicalTrials.gov registry (NCT02818101; 29/06/2016) and with the ANSM (IDRCB 2016-A00205-46; 02/02/2016).